Magnitude of Child Food Insecurity, Its Association with Child Immunization and Huosehold wealth Status, and Coping Strategies In Dabat Demographic and Surveillance System North West Ethiopia - Nigusie Birhan Tebeje; Gashaw Andargie Biks; Solomon Mekonnen Abebe; Melike Endris Yesuf (International Journal of Pediatrics)
Background. The magnitude of food insecurity in Ethiopia ranges from 38.7% to 82.3% among the general population. Children under the age of five years were more prone to food insecurity and its serious consequences like anemia, low bone density, frequent episodes of common cold, stomachache, poor educational performance, and dental carries in developing countries like Ethiopia. However, there is no any research finding that documented the magnitude of child food insecurity, coping strategies, and associated factors in the study area. Therefore, the aim of this study was estimating the magnitude of child food insecurity, major coping strategies, and factors associated with child food insecurity in the study area. Methods. A community-based cross-sectional survey has been conducted in Dabat demographic and health surveillance site among 7152 mothers/caretakers of children under the age of five years. Data were collected by experienced data collectors working for the demographic and health surveillance site, and the collected data were entered into EpiData template and then transported to Stata 14 software for data cleaning and analysis. The ordinal logistic regression model was fitted to identify predictors for child food insecurity. Results. About 21.42% of children under the age of five years were food insecure in Dabat district of whom 57.8%, 38.6%, and 3.6% had experienced mild, moderate, and severe levels of child food insecurity, respectively. All most all 1391 (92%) of the mothers/caretakers of food insecure children had practiced food insecurity coping strategies. More than half (57%) of mothers/caretakers reduces the size of child meal as insecurity coping strategy. Child food insecurity was associated with household wealth status, parent’s education status, and maternal and child health service utilization and child feeding practices. Conclusion. A large segment of under-five children had experienced food insecurity in Dabat district, and the major coping strategy for child food insecurity was reducing meal size. Therefore, working on household wealth improvement and expansion of basic health services would improve child food security.